Литовці: походження і своєрідність за даними етномузикології - Апанавічюс, Р. (Народна творчість та етнологія, 2011)
In contrast to the prevailing opinion about connection of the formation of the Lithuanians only with the origin and the development of the culture of the ancient Balts, the hypothesis is proposed that the unknown substratum culture did have a powerful influence on the ethnogenesis of the Lithuanians and the Balts as well, as it shows a very obvious difference of the Lithuanian ethnic music.